ESTIMATION OF PATIENT LENS DOSE ASSOCIATED WITH C-ARM CONE-BEAM COMPUTED TOMOGRAPHY USAGE DURING INTERVENTIONAL NEURORADIOLOGY. Issue 2 (17th November 2018) - Kawauchi, Satoru; Chida, Koichi; Moritake, Takashi; Matsumaru, Yuji; Hamada, Yusuke; Sakuma, Hideyuki; Yoda, Shogo; Sun, Lue; Sato, Masayuki; Tsuruta, Wataro
Abstract: The purpose of this study was to investigate the dose distribution and lens doses associated with C-arm cone-beam computed tomography (CBCT), using a head phantom, and to estimate the contribution ratio of C-arm CBCT to each patient's lens dose during interventional neuroradiology ('lens dose ratio') in 109 clinical cases. In the phantom study, the peak skin doses and respective right and left lens doses of C-arm CBCT were as follows: 63.0 ± 1.9 mGy, 19.7 ± 1.4 mGy and 21.9 ± 0.8 mGy in whole brain C-arm CBCT and 39.2 ± 1.4 mGy, 4.7 ± 0.9 mGy and 3.6 ± 0.3 mGy in high-resolution C-arm CBCT. In the clinical study, the lens dose ratios were 25.4 ± 8.7% in the right lens and 19.1 ± 9.8% in the left lens. This study shows that, on average, 25% of patients' total lens dose was contributed by C-arm CBCT.